A Psychometric Analysis of the Spanish Version of the Grief Impairment Scale: A Screening Tool of Biopsychosocial Grief-Related Functional Impairment in a Salvadoran Sample - Caycho-Rodríguez, Tomás (2023)
The objective of this study was to translate and psychometrically evaluate a Spanish version of the Grief Impairment Scale (GIS) using a sample of bereaved adults from El Salvador (N = 579). The results confirm the unidimensional structure of the GIS, and solid reliability, item characteristics, and criterion-related validity, where the GIS scale significantly and positively predicts depression. However, this instrument only showed evidence of configural and metric invariance between different sex groups. Overall, these results support the Spanish version of the GIS as a psychometrically sound screening tool for health professionals and researchers to use in their clinical work.